Comparing Needed and Actual Knowledge of Elder Abuse for Law Enforcement Officers, APS Workers, and Students in Criminal Justice and Social Work - Tapp, Susannah (2013)
A sample of APS workers, law enforcement officers, criminal justice and social work students were surveyed. Participants were asked how much knowledge they believed professionals working in their respective fields had about elder abuse and how much those same professionals needed to know. The differences between needed and possessed knowledge, also referred to as level of anomie, was compared across groups. Students in both groups believed those working in their fields had significantly less knowledge than they needed on all elements of responding to elder abuse. APS workers and law enforcement officers felt those in their fields had enough knowledge on some elements of responding to elder abuse but not others. APS workers had the least total anomie, and criminal justice students had the most. All groups experiences significant levels of anomie on some elements of responding to elder abuse and neglect, suggesting more training is needed